Characterization and classification of estuarine suspended particles based on their inorganic/organic matter composition - Safar, Z.; Chassagne, C.; Rijnsburger, S.; Sanz, M. Ibanez; Manning, A. J.; Souza, A.J.; van Kessel, T.; Horner-Devine, A.; Flores, R.; McKeon, M.; Pietrzak, J.D. (Frontiers in Marine Science, 2022)
A 13h survey was performed on the 17th of September 2014 in the Rhine region of Freshwater Influence (Rhine-ROFI) about 10 km downstream of the mouth of the Rotterdam Waterway during calm weather conditions. Suspended Particle Matter (SPM) measurements were performed during a full tidal cycle, near the seabed, at neap tide, and samples were taken at 0.6 m above meter for on-board analysis. The measurements were performed with (a) a LISST 100X submersible particle size analyzer, (b) a LISST-HOLO a submersible digital holographic camera, (c) a home-made underwater camera and (d) an on-board LabSFLOC2 video microscopy equipment that used in-situ collected samples.